ESTUDO SOBRE DOENÇAS SEXUALMENTE TRANSMISSÍVEIS EM ESTUDANTES UNIVERSITÁRIOS - Silvio Augusto Margando
This is a study about the sexual behaviour and venereal illnesses in undergraduate students of an university in São Paulo.